Analysis Of Factors Influencing Consumer Purchase Intention For Electric Cars: A Case Study In Greater Jakarta - Anissa Clarita; Dony Abdul Chalid (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The demand for electric cars has significantly increased in recent years, but it represents only a small fraction of the total new vehicles sold globally. This study aims to analyze the factors influencing consumer purchase intentions towards electric cars in the Greater Jakarta area (Jabodetabek). Using a survey method, data were collected from individuals who are considered capable of purchasing electric cars, either through installment plans or cash payments, and analyzed using partial least squares structural equation modeling (PLS-SEM) to test the research hypotheses. The results indicate that government incentives, ease of access to charging infrastructure, perception of resale value, product diversification, social influence, environmental concern, and consumer attitudes significantly and positively influence purchase intentions towards electric cars. However, the perception of purchase price did not show a significant effect. The findings suggest that strategic initiatives by policymakers and manufacturers, such as continuous government incentives, expansion of charging infrastructure, and effective marketing strategies leveraging social influence and environmental benefits, are crucial for promoting electric car adoption in Jabodetabek. This study provides valuable insights for understanding consumer behavior towards electric cars in emerging markets and offers useful information for enhancing market penetration.